The intersphincteric abscess as a cause of chronic anal pain. - Bermúdez Villegas, Jorge; Veirano, Gustavo; Rompani, Omar (Cirugía del Uruguay, 1985)
The intersphincteric abscess is a certain and sure cause of chronic anal pain. The authors have found it in 12 cases out of a series of 123 patients suffering from abscesses and/or perianal fistula.